Postoperative Morbidity of Dental Paediatric Patients Treated under General Anaesthesia at a University Hospital: An Observational Study - Lamis D. Rajab; Aseel E. Obaid; Mahmoud A. M. Hamdan; Yazan Hassona (Hindawi Limited, 2022)
Aims. To assess prevalence of postoperative morbidity signs and symptoms in children treated under GA, and to investigate the association between pre- and intra-operative factors with postoperative morbidity. Study design and Methods. Prospective, observational study supported by pre-operative, intra-operative, and postoperative questionnaire conducted on paediatric patients treated for dental reasons under general anaesthesia at a university hospital. Results. Hundred and fifty patients were included with average age 5.5 years. The majority (92%) experienced at least one postoperative morbidity sign and symptom on the day of treatment under GA and the majority of symptoms subside by the third day. Dental pain (81.3%), sleepiness (70%), and poor appetite (46.7%) were the most frequently reported. Logistic regression analysis showed that age, gender, type of treatment provided, use of LA, and duration of procedure were significantly associated with postoperative morbidity. Conclusions. Most patients experienced one or more morbidity sign/s or symptom/s during first postoperative day and the majority subsides by the third day. Dental pain and poor appetite were the most and long lasting reported. Factors that would predict the occurrence of postoperative morbidity were gender, patient's age, and duration of procedure.